Microscopic analysis of the microbiota of three commercial Phytoseiidae species (Acari: Mesostigmata) - Jason C. Sumner-Kalkun; Ian Baxter; M. Alejandra Perotti (Experimental and Applied Acarology, 2020)
Microbes associated with the external and internal anatomy of three commercially available predatory mite species— Phytoseiulus persimilis , Typhlodromips (= Amblyseius ) swirskii , and Neoseiulus (= Amblyseius ) cucumeris —were examined using light microscopy, confocal laser scanning microscopy and fluorescence in-situ hybridization (FISH). Four microbe morphotypes were observed on external body regions. These included three microfungi-like organisms (named T1, T2 and T3) and rod-shaped bacteria (T4). Morphotypes showed unique distributions on the external body regions and certain microbes were found only on one host species. Microfungi-like T1 were present in all three species whereas T2 and T3 were present in only P. persimilis and T. swirskii , respectively. T1 and T2 microbes were most abundant on the ventral structures of the idiosoma and legs, most frequently associated with coxae, coxal folds, ventrianal shields and epigynal shields. T3 microbes were most abundant on legs and dorsal idiosoma. T4 microbes were less abundant and were attached to epigynal shields of N. cucumeris and T. swirskii. Significant differences in distribution between batches suggest temporal fluctuations in the microbiota of phytoseiids in mass-reared systems. FISH showed bacteria within the alimentary tract, in Malpighian tubules and anal atria. These may aid absorption of excretory products or maintaining gut physiology. We suggest a mechanism by which microbes may be transmitted to offspring and throughout populations. This study aims to improve our knowledge of this poorly understood area and highlights the necessity of understanding the microbiota of Acari.